1991
DOI: 10.1093/jpepsy/16.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Child Illness, the Parenting Alliance, and Parenting Stress

Abstract: Assessed relationship between children's minor illnesses during the first 3 years of life and parenting stress in the 4th year. Also examined whether a good parenting alliance would compensate for or moderate this relationship. Parents of 56 3- to 4-year-olds completed parenting alliance and stress questionnaires. Child morbidity, assessed from medical records, was directly related to mothers' but not fathers' feelings of stress. The parenting alliance was more strongly related to parenting stress for fathers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…A stronger parenting alliance has been associated with less parenting stress in parents of ill children, as well as with fewer difficulties attaching to the child, greater competence and less restriction in the parenting role, and more perceived reinforcement from their children (Frank et al, 1991). Parenting alliance has also been linked to better parenting, by fostering self-worth and enabling parents to manage the psychological demands of parenting (Cohen & Weissman, 1984).…”
Section: The Parenting Alliancementioning
confidence: 99%
“…A stronger parenting alliance has been associated with less parenting stress in parents of ill children, as well as with fewer difficulties attaching to the child, greater competence and less restriction in the parenting role, and more perceived reinforcement from their children (Frank et al, 1991). Parenting alliance has also been linked to better parenting, by fostering self-worth and enabling parents to manage the psychological demands of parenting (Cohen & Weissman, 1984).…”
Section: The Parenting Alliancementioning
confidence: 99%
“…Les percep tions pa ter nel les de l'al liance pa rais sent par ti cu liè re ment liées au deve nir de l'en fant, y com pris à l'at ta che ment à l'en fant rap porté par le père, et au fonc tion ne ment po si tif de l'en fant tel qu'éva lué par les mè -res, les pè res et les en sei gnants (Abi din et Brun ner, 1995). En fait, certai nes preu ves sug gè rent que les pè res qui ont une al liance pa ren tale réus sie éprou vent iro ni que ment une vul né ra bi lité ac crue au stress ; ils ont mon tré des ni veaux plus éle vés de stress quand l'en fant est ma lade que les pè res qui sont moins sa tis faits de l'al liance (Frank et al, 1991). Les pè res rap por tant une al liance pa ren tale plus forte peu vent être des pa rents plus im pli qués ; leur vie est trou blée par la ma la die de leurs enfants, à la fois émo tion nel le ment et parce qu'ils pren nent congé de leur tra vail pour soi gner l'en fant.…”
Section: L'al Liance Pa Ren Taleunclassified
“…Although there has been some research linking minor illnesses during early childhood to family functioning (Forgays et al, 1992;Frank et al, 1991;Vernon-Feagans and Wamboldt, 1999), there are few studies in this area. It may not be the amount of child illness in and of itself that impacts families, but children's symptoms and parental perceptions of these illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining the effects of minor childhood illness on families is scarce. Frank et al (1991) explored the relationship between minor illness and parent characteristics in a sample of two-parent families in which 70% of the mothers were employed full-time. The authors found that child illness was linked to mothers' reports of parenting stress but not to fathers'.…”
Section: Health Statusmentioning
confidence: 99%